The Need for Islamic Information Management in the Information Institutions in Malaysia: an Analysis of Problems - Mohd Nazir Ahmad; Siti Fatahiyah Mahamood; Mohd Noor Mamat; Mashitah Sulaiman (Universiti Sains Islam Malaysia, 2024)
Presenter from Faculty of Information Management, Universiti Teknologi MARA (UiTM),Centre for Islamic Thought & Understanding, INTEC Shah Alam,Centre of General Studies,and Islamic Science University of Malaysia